Spring constant measurement using a MEMS force and displacement sensor utilizing paralleled piezoresistive cantilevers. (20th February 2018) - Kohyama, Sumihiro; Takahashi, Hidetoshi; Yoshida, Satoru; Onoe, Hiroaki; Hirayama-Shoji, Kayoko; Tsukagoshi, Takuya; Takahata, Tomoyuki; Shimoyama, Isao
Abstract: This paper reports on a method to measure a spring constant on site using a micro electro mechanical systems (MEMS) force and displacement sensor. The proposed sensor consists of a force-sensing cantilever and a displacement-sensing cantilever. Each cantilever is composed of two beams with a piezoresistor on the sidewall for measuring the in-plane lateral directional force and displacement. The force resolution and displacement resolution of the fabricated sensor were less than 0.8 µ N and 0.1 µ m, respectively. We measured the spring constants of two types of hydrogel microparticles to demonstrate the effectiveness of the proposed sensor, with values of approximately 4.3 N m −1 and 15.1 N m −1 obtained. The results indicated that the proposed sensor is effective for on-site spring constant measurement.